Work Engagement, Perceived Organizational Support, and Organizational Behaviors Influenced Intention to Stay among Officers at MKK Hospital, Jakarta - Lydia, Lydia; Dewi, Sandra; Pamungkas, Rian Adi (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: During the pandemic, most nurses withdrew/resigned from service (turnover). Objective: The study aimed to analyze the effect of work engagement, perceived organizational support, and organizational culture on the intention to stay of MKK Hospital employees. Method: This quantitative study uses a survey approach to examine the causal effects of work engagement, perceived organizational support, and organizational culture on the intention to stay of employees at MKK Hospital, Jakarta. This study's population was all MKK Jakarta Hospital employees, totaling 418 people. The sample in this study was 213 MKK Hospital employees consisting of nurses. Result: The results showed an effect of work engagement, perceived organizational support, and organizational culture on intention to stay among employees at MKK Hospital. Conclusion: The conclusion showed that work engagement has the most significant influence, followed by organizational culture and perceived organizational support influencing the intention to stay in MKK Hospital employees. Recommendation: This research helps hospital management, especially the Human Resources department, to design programs, formulate strategies and start employee organizational development to strengthen/increase employee retention or intention to stay in hospital employees in Indonesia, especially MKK Hospital